ANALISIS PERAN DAN UPAYA GURU DALAM MENGATASI PERMASALAHAN BELAJAR SISWA KELAS II SDN 1 SULAHAN TAHUN 2023 - Pradnyana, Putu Beny; Amanda, Sang Ayu Putu Gita (Dharmas Education Journal (DE_Journal), 2023)
Learning problems refer to situations where students face challenges in following the learning process, thereby causing dissatisfaction in learning achievement. This is caused by an imbalance between students' skills in completing assignments and the learning demands given. This research aims to describe the role and efforts of teachers in overcoming learning problems in second grade. This type of research is qualitative research with data analysis methods using observation and interview techniques. The research instruments used were interview grids and data recording cards. The subject of this research is a second grade teacher. Results from the first research, to overcome students' reading difficulties, this can be done through personal coaching or counseling. Second, when dealing with students who are not yet proficient in writing, teachers can provide motivation as an effective action and provide practice. Third, to overcome students' concentration difficulties, teachers can adopt more diverse learning media. Fourth, in helping children with special needs, implementing inclusive education can be an effective strategy and provides practice or repetition. Fifth, to overcome low student motivation, teachers can use school facilities, such as studying in the school yard or in the library, and utilize various learning methods. The teacher's role and efforts in overcoming the learning problems faced by each student are different because it depends on the problems the student faces.